Basic Clause Structure in Sikka - Radjalewa, Cosmas; Suhandano (Fakultas Bahasa Asing (FBA) Universitas Mahasaraswati Denpasar, 2025)
This study aims to describe the basic clause structure in Sikka and identify the syntactic implications of the basic clause structure in Sikka. The primary data of the study were obtained from fieldwork interviews with two Sikka native speakers in Koting C village and Kokowahor village, online correspondence with one Sikka speaker, and introspection. The secondary data was taken from written texts in Sikka. The data were analyzed using transitivity alternation and work order pattern as the primary theoretical framework in this study. The result shows that Sikka has three types of basic clause structures distinguished by verb type (transitivity) and the number of core arguments involved in a clause (valency). The first basic clause type in Sikka is the intransitive clause (IC). ICs are clauses with one core argument (S). The second type is the transitive clause (TC). TC is a clause with two core arguments (A and O). The third type is the ditransitive clause (DC), which has three core arguments (A, PO, and SO. The predicate in DC can be a typical ditransitive verb or a serial verb construction (SVC). The results of basic clause structure identification in Sikka shed light on typological claims such as voice alternation and valency-changing mechanisms that distinguish languages in Eastern Indonesia from languages in Western Indonesia.